A Study of Factors Influencing Customers’ Adoption of Mobile Banking in Oman - Tahir, Muhammad; Tummala, Mallesh (Advances in Social Sciences Research Journal, 2022)
The commercial banking sector in Oman is a dynamic sector with a large number of banking service users. However, the customers’ adoption of technology in terms of online banking and mobile banking remains less due to the various socio-demographic factors. Given the cost and operational benefits of mobile banking, there is a need to understand how commercial banks can motivate non-mobile banking users to adopt mobile banking in this context. Thus, the current study is conducted with a view to understand customers’ adoption of mobile banking using the Perceived Characteristics of Innovation model. The data is collected from the commercial bank account holders who are non-users of mobile banking (n=80). The key findings are that perceived ease of use (β=.487, P<.05); and observability (β=.530, P<.05) positively and significantly influence customers intention to use mobile banking; whereas, relative advantage (β=-.068, P>.05); compatibility (β=-.413, P>.05); and trialabiltiy (β=.371, P>.05) exert insignificant influence on customers intention to use mobile banking. Based on these findings, it can be concluded that perceived ease of use and observability are key factors which commercial banks need to focus to encourage customers to adopt mobile banking.